INVESTIGATING MEDICAL STUDENTS’ DIFFICULTIES IN TOEFL LISTENING TEST - Fauza A. Rahmi; Usman Kasim; Zulfadli A. Aziz (Universitas Syiah Kuala, 2020)
This research investigated the students’ responses to listening difficulties in taking the listening section of the TOEFL test and their efforts made to overcome the difficulties. This study is descriptive qualitative research that used the online questionnaire attached in the google forms to gather data needed. The questionnaire was distributed to 100 medical students at UP3BI class (Unit Pengembangan Program Pendamping Mata Kuliah Bahasa Inggris (UP3BI) of Syiah Kuala Language Center. The questionnaire was divided into two. Part one consisted of students’ personal information on the listening skill questionnaire. It was found that watching English TV programs or movies (65.10%) and listening to English songs (60%) as the highest rank of students’ efforts made to overcome listening difficulties of the TOEFL test. Section two of the questionnaire consisted of listening difficulties. It was found that most respondents were difficult to understand the native speaker’s pronunciation (64%). In addition, it is suggested that for English lecturers, other researchers, institutions, and testing organizers to contribute a standardized knowledge of the TOEFL test and also to provide a conditioned testing place for a better improvement of listening TOEFL in particular. Besides, the test takers or students should practice and learn more about listening TOEFL as often as possible. Therefore, they will get used to listening and can minimize the difficulties during taking the TOEFL test.